Antimicrobial activity of Indian Oregano (Coleus Aromaticus) against Diabetic wound pathogens - Kalesware A/P Muniandy (Universiti Sains Islam Malaysia, 2024)
Thesis (M.Sc)--Faculty of Science and Technology, Universiti Sains Islam Malaysia, 2015